2004
DOI: 10.1080/02660830.2004.11661487
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of prior vocational learning in Sweden

Abstract: Initiatives in the recognition of prior learning (RPL) have been taken in Sweden in recent years, mainly focusing on prior vocational learning among immigrants. The government started different projects to find methods for recognising a person's prior learning in the field of vocational competence. This article presents a study of how these projects were organised and their starting points. Differences are identified concerning whether they were integrated with, or parallel to, the school system, and whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…One point is that credits for vocational competence could be awarded to those with no or limited formal education, but there is also a need for cultural changes in the workplace to enhance learning and development (Davies 1999). Recent initiatives have been taken in recognition/validation of prior vocational learning in Sweden, which place the focus on the influence of the school tradition of grading, and the important role of the Swedish language in assessing competence (Andersson et al 2004). The French history of validation seems to include a broader and more holistic approach than the British tradition, which also leads to a discussion about the universalistic claim of a somewhat Western individualistic approach (Pouget and Osborne 2004).…”
Section: Research On Validation Assessment and Foucaultmentioning
confidence: 99%
See 1 more Smart Citation
“…One point is that credits for vocational competence could be awarded to those with no or limited formal education, but there is also a need for cultural changes in the workplace to enhance learning and development (Davies 1999). Recent initiatives have been taken in recognition/validation of prior vocational learning in Sweden, which place the focus on the influence of the school tradition of grading, and the important role of the Swedish language in assessing competence (Andersson et al 2004). The French history of validation seems to include a broader and more holistic approach than the British tradition, which also leads to a discussion about the universalistic claim of a somewhat Western individualistic approach (Pouget and Osborne 2004).…”
Section: Research On Validation Assessment and Foucaultmentioning
confidence: 99%
“…It was possible to assess knowledge gained through informal learning and non-formal education, to assess what had been learnt at work and at home, as well as in other countries. The possibility of validation of foreign vocational competence (Andersson et al 2004), to make it easier for immigrants to enter the Swedish labour market, was one of the main arguments for validation (SOU 1998:165, SOU 2001. Another main argument was to make education shorter and cheaper -you do not have to study what you have already learnt and that can be assessed through validation.…”
Section: A History Of Validationmentioning
confidence: 99%
“…Although we consider the above two approaches applied by Andersson et al (2004) and Harris (1999) as relevant for understanding RVA, we argue, however, that convergent and divergent models are not static categories; rather they are evolving. For example, while RPL in South Africa, on the one hand, is highly standardised and centralised through being closely associated with the South African Qualifications Authority (SAQA), on the other hand it recognises the different strategies in implementing RVA for different target groups -"access", "redress" and "credit/qualification attainers" (SAQA 2012b).…”
Section: Convergent and Divergent Or Parallel Modelsmentioning
confidence: 99%
“…Andersson et al (2004) have identified two main types of recognition models: recognition which is adapted to the education and training system (convergent), and recognition that is oriented towards changing the system (divergent). Harris (1999) explores RPL practices in the South African higher education context in terms of its application as a mechanism to change the system.…”
Section: Convergent and Divergent Or Parallel Modelsmentioning
confidence: 99%
“…When the initiative ended, state funds to the municipals were reduced, as was the number of study places for adults. Today, new ways to develop adult education are being discussed, especially recognition of prior learning (for further reading, see Andersson, Fejes and Ahn 2004).…”
Section: Swedish Adult Educationmentioning
confidence: 99%